Uveitis in Patients with Ankylosing Spondylitis - Bisht, Anjal; Shrestha, Samrat; Bajgai, Priya; Khadka, Milan; Koirala, Parimal; Bhattarai, Kumud (Journal of Nepal Health Research Council, 2021)
Background: There is a close correlation between ankylosing spondylitis and uveitis, other less common ocular manifestations being episcleritis and scleritis. Though the prognosis of uveitis is good, prompt treatment is required to prevent long-term complications. This study aimed to estimate the prevalence of uveitis in patients with ankylosing spondylitis who follow outpatient clinic of a tertiary care hospital.Methods: A descriptive cross-sectional study was done in medicine outpatient department of a tertiary care hospital for 6 months. Ethical clearance was obtained from the institutional review board of National Academy of Medical Sciences. Convenient sampling was done. The data collected were entered in Microsoft excel to tabulate the data and analyze the results.Results: Out of 81 participants, 26 patients had a history of uveitis (32%). Most of the patients in this study were of 18-30 years. Uveitis was most common in patients with both axial and peripheral disease (41%) compared to those with just peripheral disease (32%). Uveitis was more common among males (32.2%) than females (31.5%).Conclusion: In patients with spondyloarthritis uveitis was present in 32% of the patient with more common in patient with both axial and peripheral arthritis. Timely diagnosis of uveitis in ankylosing spondylitis can prevent the sequelae with prompt treatment. Keywords: Ankylosing spondylitis; spondyloarthritis; uveitis